The century of the Holy Spirit: 100 years of Pentacostal and charismatic renewal, 1901-2001 - Synan, Vinson (Thomas Nelson, 2001)
"A definitive history of the Pentecostal and Charismatic movement and an intriguing reference for persons outside the movement, The Century of the Holy Spirit details the miraculous story of Pentecostal / Charismatic growth--in the U.S. and around the world ..."--Amazon.com